2021
DOI: 10.17576/jkmjc-2021-3703-15
|View full text |Cite
|
Sign up to set email alerts
|

Netnography and Social Network Analysis: Centrality Actors Reopening Indonesia's Tourism Industry in a Transitional Era

Abstract: The Covid-19 disease that the World Health Organization (WHO) stated as a pandemic on March 11, 2020 impacts negatively on the tourism industry. It causes the foreign exchange earnings from the tourism sector to decline, and it is the duty of the Ministry of Tourism and Creative Economy to resolve this problem . The implementation of physical distancing as a solution to minimize the spread of the Covid-19 disease has changed society to do more activities online which speeds up the development of digital cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In carrying out this research, an objective, valid, reliable, and replicable systematic identification of the visible (manifest) communication content is conducted (Eriyanto, 2011). Additionally, the netnography method was employed to gain a deeper understanding of netizens' culture, interactions, and activities in cyberspace (Fitriyah & Nurhaeni, 2021;Irawan, 2022). Netnography enables the researcher to uncover non-verbal responses to netizen messages (Başaslan & Aydn, 2022) or comments in the comments section on the TikTok account of Ustadz Syam.…”
Section: B Methodsmentioning
confidence: 99%
“…In carrying out this research, an objective, valid, reliable, and replicable systematic identification of the visible (manifest) communication content is conducted (Eriyanto, 2011). Additionally, the netnography method was employed to gain a deeper understanding of netizens' culture, interactions, and activities in cyberspace (Fitriyah & Nurhaeni, 2021;Irawan, 2022). Netnography enables the researcher to uncover non-verbal responses to netizen messages (Başaslan & Aydn, 2022) or comments in the comments section on the TikTok account of Ustadz Syam.…”
Section: B Methodsmentioning
confidence: 99%
“…Netnography is a qualitative research method that studies online communities, interactions, and cultures where involvement ranges from observing online conversations to actively participating in social media [24]. The netnography method is used to understand social relations in social networks and analyse the structure and pattern of relationships between community members called actors (nodes) and relationships between members called ties [25]). Nodes or actors refer to people or messages, whereas Tide can describe the relationship between actors-for example, a bond to share information, ideas, and values [26].…”
Section: Social Network Analysis and Two Step Flow Theorymentioning
confidence: 99%
“…Russo et al (2008) elucidated that social media facilitate online communications, networking, and collaborations. Social media are also employed as a public relation tool to communicate and exchange ideas (Fitriyah et al, 2020), express personal thoughts or opinions, exchange information with other users, and influence or manipulate users to accept generated content (Fitriyah & Nurhaeni, 2021). According to Taprial and Kanwar (2012), social media are a powerful medium, as individuals require constant communication by perusing, listening, and responding to opinions and perspectives shared on social media.…”
Section: Literature Review 21 Social Mediamentioning
confidence: 99%
“…The analysis could observe the community structure, depict the network structure, and visualise the relationship between social agents before developing a research model (Su et al, 2020). Previous studies demonstrated social networks operating at various levels ranging from a group of families to nationally (Fitriyah & Nurhaeni, 2021;Gandasari et al, 2018Gandasari et al, , 2022Hicks et al, 2020;Selden & Goodie, 2018). Thus, the SNA plays a critical role in determining problem-solving solutions, organisational processes, and the extent of individuals' success in goal accomplishment (Mastan & Christianto, 2021).…”
Section: Social Network and Social Network Analysismentioning
confidence: 99%